2001
DOI: 10.1034/j.1600-0714.2001.300902.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of oral and pharyngeal cancers in the Basque Country

Abstract: Oral and pharyngeal cancer is an entity constituted by a group of tumours that arise in several heterogeneous anatomical sites, and for this reason it is difficult to establish comparisons. The aim of the study was to describe the characteristics of oropharyngeal cancer in the Basque Autonomous Community (BAC), to learn the incidence rate and to establish comparisons. Data of cases are from the Basque Country Cancer Registry for the period 1986-1994, and the methodology used is descriptive. We included 2548 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 7 publications
3
11
2
Order By: Relevance
“…In our series these neoplasms constitute 94.9%, a slightly larger percentage than that described by Izarzugaza et al (91.7%), whose series included the base of tongue (18). …”
Section: Discussioncontrasting
confidence: 53%
“…In our series these neoplasms constitute 94.9%, a slightly larger percentage than that described by Izarzugaza et al (91.7%), whose series included the base of tongue (18). …”
Section: Discussioncontrasting
confidence: 53%
“…Regarding the frequency of oral and pharyngeal cancer, Izarzugaza et al (2001) reported that in the Basque Country, Spain, squamous cell carcinoma was found in 95% of the 2548 tumours of the head and neck. But oral and pharyngeal cancer arise in several heterogeneous anatomical sites, and for this reason it is difficult to establish comparisons with other sites.…”
Section: Discussionmentioning
confidence: 98%
“…Insufficient melanin also appears to explain the high proportion of lip squamous cell carcinoma in White persons with a fair complexion 3,11,13,19 . This is exacerbated by actinic radiation.…”
Section: Discussionmentioning
confidence: 98%